2021
DOI: 10.3399/bjgpo.2021.0068
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported knowledge of national guidelines for clinical screening for hip dysplasia: a web-based survey of midwives and GPs in Denmark

Abstract: BackgroundThe positive predictive value of clinical hip examinations performed by generalist health professionals in screening for developmental dysplasia of the hip (DDH) is low.AimTo assess the self-reported recognition of nationally recommended clinical hip examinations in the screening programme for DDH in Denmark among midwives, general practitioners (GPs), and GPs in training.Design & settingA web based open survey study among Danish midwives, GPs and GPs in trainingMethodRespondents were asked to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
(22 reference statements)
0
3
0
1
Order By: Relevance
“…Since the Cochrane review was published, evidence increasingly points towards limitations in the selective screening approach, as 85% of patients treated for DDH do not fulfill the criteria for selective ultrasound screening [ 6 ]. Further, primary screeners have insufficient knowledge of the clinical examinations and risk factors which constitute the foundation of the selective screening approach [ 7 , 8 , 9 ]. These findings might explain why 26 years of selective ultrasound screening in the UK has failed to reduce the rate of late DDH diagnoses.…”
Section: Introductionmentioning
confidence: 99%
“…Since the Cochrane review was published, evidence increasingly points towards limitations in the selective screening approach, as 85% of patients treated for DDH do not fulfill the criteria for selective ultrasound screening [ 6 ]. Further, primary screeners have insufficient knowledge of the clinical examinations and risk factors which constitute the foundation of the selective screening approach [ 7 , 8 , 9 ]. These findings might explain why 26 years of selective ultrasound screening in the UK has failed to reduce the rate of late DDH diagnoses.…”
Section: Introductionmentioning
confidence: 99%
“…However, also other factors might have played a role. A survey of primary screeners in Denmark revealed that the Ortolani manoeuvre was the only widely known clinical hip examination 20 . The screeners did not recognise correct statements from false statements produced by the investigators regarding the Danish guidelines for screening.…”
Section: Discussionmentioning
confidence: 99%
“…A survey of primary screeners in Denmark revealed that the Ortolani manoeuvre was the only widely known clinical hip examination. 20 The screeners did not recognise correct statements from false statements produced by the investigators regarding the Danish guidelines for screening. It is possible, that some of the Barlow tests were mis-interpreted as positive in the present study.…”
Section: F I G U R E 1 (A)mentioning
confidence: 96%
“…-в Германии в качестве метода общего обследования всех новорожденных [8,9]. В США, Великобритании, скандинавских странах ультрасонография проводится селективно новорожденным группы риска [10,11,12]. В настоящее время существует несколько методик УЗИ ТБС: Графа, Харке, Сузуки, Тержесена и т.д.…”
Section: Introductionunclassified